Experimental research of a new CFRP-based shear strengthening technique for reinforced concrete beams - Dias, Salvador J. E. (2005)
A Near Surface Mounted (NSM) strengthening technique was developed to increase the shear resistance of reinforced concrete beams. The NSM technique is based on fixing, by epoxy adhesive, CFRP laminate strips into saw-cut slits on the concrete cover of lateral surfaces of the beams. To assess the efficacy of this technique, an experimental program of fourpoint bending tests was carried out. Each of the four tested series was composed of five beams: without any shear reinforcement; reinforced with conventional steel stirrups; strengthened with U strips of wet lay-up CFRP sheets; and two beams strengthened with precured laminate strips of CFRP, one of them with laminates positioned at 90º and the other with laminates positioned at 45º in relation to the beam axis. Influences of the laminate strip percentage, laminate strip inclination and beam height on the efficacy of the NSM technique were analyzed. This efficacy was assessed not only in terms of the increase of maximum load and deflection at beam rupture, but also in terms of the beam strength performance per unit length of the applied material.